Masyarakat Madani Perspektif Al-Qur’an: Prinsip-prinsip Pembentukan dan Relevansi di Era Modern - Andi Sitti Emeralda Ria; Muhammad Yusuf; Hasyim Haddade (Refleksi: Jurnal Kajian Agama dan Filsafat, 2025)
This article presents an in-depth analysis of the concept of madani society (civil society) from the Qur’anic perspective, understood as an ideal social order founded upon justice, welfare, and democratic values. The study aims to formulate the fundamental principles underlying the formation of a madani society and to underscore their relevance in responding to the challenges of globalization, pluralism, and shifting power dynamics in the modern era. The research employs a qualitative methodology based on library research with a descriptive-thematic (mawḍū‘ī) analytical approach. Primary data are drawn from key Qur’anic verses—Q. al-Nisā’ 58, al-Ḥujurāt 13, al-Shūrā 38, and al-Baqarah 143—supported by authoritative exegetical works by Ibn Kathīr, al-Qurṭubī, and Sayyid Quṭb. The findings indicate that the conceptual blueprint of a madani society is constructed upon four foundational principles: (1) justice as the ethical and legal cornerstone; (2) equality of human dignity, which rejects discrimination and affirms diversity; (3) consultation (shūrā) as a participatory political mechanism to prevent authoritarianism; and (4) moderation (ummatan wasaṭan) as a moral and spiritual framework. The study argues that these principles position madani society as an essential counter-power through the implementation of amr bi al-ma‘rūf wa nahy ‘an al-munkar as a form of social accountability. Consequently, the Qur’anic conception of madani society offers not only a theoretical framework but also an ethical-operational foundation for establishing a just, harmonious, and inclusive social order in contemporary contexts.